MODEL PEMBINAAN BUDI PEKERTI SISWA SEKOLAH DASAR MELALUI PENDEKATAN KULTURAL - Arif Purnomo; Ubaidillah Kamal; Elly Kismini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2002)
The aim of research can be formulated : (1) to knowing what kind of situations. the ceacher of the elementary school students carry out the construction of morals to the students, (2) 10 knowing the cultural approach be used to construction of the students morals, and (3) 10 knowing students respons as the teacher carry out the construction of students morals. This research employed the qualitative approach. With this approach, it was expected that a clear description of the meaning of the reality would be obtained. The data were col• lected through observation, interviews and documentation. The data analyses in this study covered the domain, componential, taxonomy, and the matic analyses. Bassed on the findings of the research, it can be concluded that, first, the construction of the morals 10 the students incidentally and without planning in instructional objective. This situation is considered 10 be effective because the effort to educate students 10 understand good or bad behaviour can be done at the time of the occurence so that the students will remember and will not repeat it. Secondly, the cultural approach to construction of morals had to applicated with touch the students feeling by description of high cultural forefather, and (3) the construction bf morals by cultural approach in the teaching learning process gave different nuance to the students. From the findings of research above, it can be suggested that, first, the teachers in elementary school have to concern of all thems behaviour in school, because it can be easily and faster imatate all word and appearance of the teacher, and finally, the teacher have to plan in instructional objective his affectivelly goal, specially to relate with the moral values.